KLASIFIKASI STATUS GIZI MENGGUNAKAN NAIVE BAYESIAN CLASSIFICATION - Kusumadewi, Sri (Bina Nusantara University, 2009)
Until recently, Body Mass Index (BMI) has been used as a method for measuring the nutrient state of an individual. Two people having the same weight and height may have different nutrient states. Whenever this occurs, the use of BMI for measuring the nutrient state shall be deemed irrelevant. The anthropometry will be vital in measuring the nutrient state. On the contrary, as the development of IT progresses, so does the improvement of numerical computation. One of the computational algorithms that have been improving is probabilistic reasoning with Naive Bayesian Classification (NBC) as its method. This algorithm is intended to data classification. In this research, the NBC algorithm will be applied for measuring the human nutrient status by using anthropometry data as input system. The result of this research shows that NBC can solve this problem adequately. Research results shows total performance of this system as 93.2%.Keywords: classification, Naive Bayesian Classification (NBC), nutrition